2003
DOI: 10.1148/radiol.2273020111
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Osteoid Osteoma with Dynamic Gadolinium-enhanced MR Imaging

Abstract: Osteoid osteomas can be imaged with greater conspicuity by using dynamic gadolinium-enhanced instead of nonenhanced MR imaging and with conspicuity equal to or better than that obtained with thin-section CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(88 citation statements)
references
References 21 publications
2
77
0
9
Order By: Relevance
“…These results also support the previous findings of Barei et al (36), who investigated similar items in a small series of patients. Our relatively uniform CT and preprocedural MRI patterns were in agreement with the literature (16,(37)(38)(39)(40)(41)(42), but the follow-up (mean, 3.4±2.2 months) MRI varied considerably. In Figure 4.…”
Section: Discussionsupporting
confidence: 90%
“…These results also support the previous findings of Barei et al (36), who investigated similar items in a small series of patients. Our relatively uniform CT and preprocedural MRI patterns were in agreement with the literature (16,(37)(38)(39)(40)(41)(42), but the follow-up (mean, 3.4±2.2 months) MRI varied considerably. In Figure 4.…”
Section: Discussionsupporting
confidence: 90%
“…The pattern of dynamic enhancement of non-treated osteoid osteomas on MRI has been studied in detail by Liu et al [7]. They assessed the morphology or type of enhancement curve, and found that nine of 11 patients (82%) had peak enhancement of the osteoid osteoma in the early arterial phase with early partial wash-out.…”
Section: Discussionmentioning
confidence: 99%
“…The radiolucent nidus is best seen on thin slice (1 mm to 2 mm) axial CT images, because there is no overlap of surrounding reactive sclerosis and/or periosteal reaction [3][4][5]. More recent papers have focused on the appearance of osteoid osteoma on magnetic resonance imaging (MRI), describing the morphology of the nidus, the surrounding bone, and the adjacent soft tissues, as well as the enhancement pattern of the nidus during dynamic MRI imaging [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Its application in musculoskeletal radiology is mainly limited to the assessment of tumors (18)(19)(20). Information about the vascularity and…”
Section: Patientsmentioning
confidence: 99%